Developing Recommendations to Guide Future Evidence Generation, Evidence Synthesis, and Knowledge Translation for Rare Diseases - Tingley, Kylie (Université d'Ottawa / University of Ottawa, 2021)
Introduction: The scarcity of rigorous evidence regarding rare disease therapies contributes to uncertainty for stakeholders who make decisions about the use, prescription, or funding of such therapies. My dissertation objective was to integrate stakeholder perspectives and evidence related to how rare disease therapies are evaluated to better understand drivers of uncertainty in decision making and develop an evaluation framework for future evidence generation, synthesis, and decision support. Methods: To better understand the perceived challenges in generating robust treatment effectiveness evidence, and describe various methods for mitigating these challenges, I used a meta-narrative literature review. I also conducted focus group interviews with key rare disease stakeholders (patients/caregivers, physicians, and policy advisors) to elicit different perspectives on how evidence is generated, evaluated, and synthesized in the context of health care decision making, both at a personal and population level. Finally, I integrated the focus group findings with a targeted literature review to identify characteristics of rare diseases and their candidate therapies that may warrant special consideration in health technology assessment (HTA) and health care decision making. Findings: My dissertation data revealed three fundamental challenges in generating robust treatment effectiveness evidence for rare diseases: limitations in recruiting a sufficient sample; inability to account for clinical heterogeneity; and reliance on outcomes with unclear clinical relevance. Several methodological solutions have been proposed to overcome these challenges. In addition, study participants described different perspectives on how they choose to participate in and use research in their roles as health care users, care providers, and policy advisors. Notably, conventional wisdom that patients/caregivers participate in clinical research studies because of therapeutic misconception was not supported. Finally, focus group and literature review findings identified information that potentially warrants special consideration in future HTA specific to rare diseases, including characteristics of the disease, understanding of causal hypotheses relevant to the therapy, and complexities of cost-effectiveness given the high price of many rare disease therapies. Discussion: Together, the findings from this dissertation support an evaluation framework with eight key principles that aim to mitigate important aspects of uncertainty from various stakeholder perspectives and promote evidence-informed decision making about rare disease therapies.
Keywords: Rare diseases; Knowledge synthesis; Epidemiology; Qualitative research